Significance of RANTES‐CCR5 axis and linked downstream immunomodulation in Dengue pathogenesis: A study from Guwahati, India. Issue 12 (12th August 2019) - Islam, Mafidul; Kalita, Trishna; Saikia, Anjan K.; Begum, Anjuma; Baruah, Vargab; Singh, Nidhi; Borkotoky, Raktim; Bose, Sujoy
Abstract: We aimed to evaluate the significance of the RANTES‐CCR5 axis and resulting immunomodulatory status in Dengue pathogenesis involving a Guwahati, India based population where Dengue cases have increased alarmingly. An increased CC‐chemokine receptor type 5 (CCR5) messenger RNA expression and CCR5 positive cell count profile was observed in Dengue cases, the highest being in severe cases. CCR5 ligand RANTES expression was significantly decreased in Dengue cases and inversely correlated with Dengue viremia fold change in severe cases. Monocytes are involved in Dengue virus homing and replication. Its levels and activation profile were higher in Dengue cases. A hyper Th1‐biased immunomodulatory profile with upregulated tumor necrosis factor‐α levels, and downregulated expression of antiviral cytokine interferon‐γ and key regulatory Th2 anti‐inflammatory cytokine interleukin 10 was observed in severe Dengue cases compared with mild Dengue cases and controls. The results, therefore, suggest the significance of RANTES‐CCR5 axis deregulation and resulting altered immunomodulation in Dengue pathogenesis, and holds prognostic and therapeutic significance. Highlight: CCR5 associated with dengue pathogenesis. RANTES downregulation is a key mediator in dengue pathogenesis. Monocyte profile changes significantly effects dengue pathogenesis. Hyper Th1 biased immunomodulation is significant in dengue severity. RANTES, TNF‐alpha expression holds prognostic and therapeutic significance.